IMPLEMENTASI PROGRAM KAWASAN RUMAH PANGAN (KRPL) DI KELURAHAN PALAS KEMATAN RUMBAI KOTA MADYA PEKANBARU - Futi Imansuri; Armaini '; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The development of food production nowadays is only focused on the rice field yard. But in fact, Indonesia still has many potentials to produce the food in the rate of 14%.Indonesian Agriculture Ministry determines “Kawasan Rumah Pangan Lestari (KRPL)” program which is applied by a women group, named Kurnia Harapan, which is located in Palas, Rumbai, Pekanbaru.This research aims to analyze the implementation of “KRPL” program, to find out the application of yard production system, and to find out the factors which affect the implementation of “Kawasan Rumah Pangan Lestari (KRPL)”.This research was conducted by using survey method and was analyzed statistically by using multiple linear regression.The research findings show that 83,3% of the implementation is categorized into medium category. The age, the range of the area, the family size and their wages as many as 34,5%, while another is affected by the other factors out of the model.The implementation of productin system has point to the general orientation of “Badan Litbang Pertanian”, but it is not determined yet for multilevel model in this women group.The factors which affect the implementation are the water availability, the medium and infrastructure, the cultivation knowledge, and the information access. Keywords: Implementation, “Kawasan Rumah Pangan Lestari (KRPL)”.